Synthesis and Characterization on Crystalline Structure and Magnetic Topology Anomaly of Nd0.75Na0.25-xKxMnO3 Manganite. - Sivananthem, Tevageran; Shamsuddin , Suhadir (Enhanced Knowledge in Sciences and Technology, 2022)
The Nd0.75Na0.25-xKxMnO3 perovskite manganite oxide with compositions, x = 0, 0.05 and 0.10 respectively have been studied scientifically to untangle the effect of K substitution at the Na-site on the crystalline structure, magnetic topology, bulk density, unit cell volume and the porosity. In addition, the correlation between X-ray diffraction (XRD) measurement and Atomic Force Microscopy measurement (AFM) was also studied. In this study, a new research approach has been introduced which was revealing the magnetic topology images of the Nd0.75Na0.25-xKxMnO3 perovskite manganite oxide that is rarely reported by previous researchers. The samples was prepared from high purity oxide powder (99.99%) maneuvering solid state reaction method and characterized by X-ray diffraction and Atomic Force Microscopy with lift mode enabled. Furthermore, the bulk density of the samples was determined using Archimedes principle and the porosity was computed using standard formula. The AFM measurements revealed the changes occurred in magnetic domains of all the samples due to the substitution of K element. Besides that, it was also observed that the varying concentration of K substitution at the Na-site of the manganite system contributed to magnetic topology anomaly of all the samples. In addition, the XRD measurements revealed the crystalline structure of all the samples which was single phased and indexed as orthorhombic structure with Pnma space group. The elemental substitution had also changed the unit cell volume, bulk density, and porosity of the samples as the increase in the concentration of K element. Hence, the correlation between the XRD and AFM measurement was noticed as the results from both measurements showed good agreement.